(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In order to influence the listener, the speaker should use not only linguistic means, but also non-linguistic means. According to the American scientist Megrabian’s formula, the positive impressions of the first interlocutors were positive for 7% of speech, 38% for paralinguistic factors and 58% for non-verbal actions. This means that nonverbal means have a direct effect on the speech process. Each nation uses its language differently in communication. The language used in Uzbek speech is different from that of other nations, reflecting Uzbek culture.